2016
DOI: 10.18632/oncotarget.10309
|View full text |Cite
|
Sign up to set email alerts
|

IGF2-derived miR-483 mediated oncofunction by suppressing DLC-1 and associated with colorectal cancer

Abstract: Emerging evidence indicates that IGF2 plays an important role in various human malignancies, including colorectal cancer (CRC). Hsa-miR-483 is located within intron 7 of the IGF2 locus. However, the mechanism by which increased IGF2 induces carcinogenesis remains largely elusive. DLC-1 has been identified as a candidate tumor suppressor. In this study, we aimed at investigating whether miR-483 transcription is IGF2-dependent, identifying the functional target of miR-483, and evaluating whether tissue and serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…22 In addition, DLC-1 induced apoptosis and inhibited the growth and invasion of colon cancer cells. 24,25 In this study, it suggested that DLC-1 was regulated by miR-301a-3p, and overexpression of DLC-1 could inhibit proliferation, invasion, and migration. 24,25 In this study, it suggested that DLC-1 was regulated by miR-301a-3p, and overexpression of DLC-1 could inhibit proliferation, invasion, and migration.…”
Section: Discussionmentioning
confidence: 72%
“…22 In addition, DLC-1 induced apoptosis and inhibited the growth and invasion of colon cancer cells. 24,25 In this study, it suggested that DLC-1 was regulated by miR-301a-3p, and overexpression of DLC-1 could inhibit proliferation, invasion, and migration. 24,25 In this study, it suggested that DLC-1 was regulated by miR-301a-3p, and overexpression of DLC-1 could inhibit proliferation, invasion, and migration.…”
Section: Discussionmentioning
confidence: 72%
“…A recent study also reported that the let-7 family of miRNAs was potential biomarkers for grade prediction in breast cancer (34). MiR-483 has an important role in suppressing the deleted in liver cancer-1 (DLC-1) gene and may thus serve as a new therapeutic target and a potential biomarker of colorectal cancer (35), and miR-494 has been demonstrated to inhibit ovarian cancer cell proliferation and promote apoptosis by targeting fibroblast growth factor receptor 2 (ref. 36).…”
Section: Discussionmentioning
confidence: 98%
“…miR‐483‐5p is expressed in multiple cancers and has been proposed as a circulating biomarker of tumor presence . In CRC it can suppress the DLC‐1 gene (deleted in liver cancer 1), inducing cell proliferation . Altered expression of miR‐186 affects tumor growth, invasion and metastasis in various cancers .…”
Section: Discussionmentioning
confidence: 99%
“…41 In CRC it can suppress the DLC-1 gene (deleted in liver cancer 1), inducing cell proliferation. 42 Altered expression of miR-186 affects tumor growth, invasion and metastasis in various cancers. 43 For this miRNA, there were significant differences in expression between plasma from patients with polyps or adenomas and controls without lesions recruited from the Bowel Cancer Screening Program in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%